Patient characteristics modify the association between changes in mineral metabolism parameters and mortality in a nationwide hemodialysis cohort study - Shunsuke Goto; Takayuki Hamano; Masatomo Taniguchi; Masanori Abe; Kosaku Nitta; Shinichi Nishi; Hideki Fujii (Scientific Reports)
Abstract In hemodialysis patients, it remains unclear whether patient characteristics influence the clinical impacts of changes in serum mineral metabolism parameters on mortality. In this 9-year cohort study, we investigated the associations between the changes in calcium/phosphate levels and all-cause mortality using a time-dependent approach after adjustment for potential confounders in groups stratified by performance status (PS), a history of atherosclerotic cardiovascular disease (ACVD), or diabetic nephropathy (DN). In patients with baseline serum calcium levels of 9.5–<10.0 mg/dL, increases in serum calcium levels were associated with higher mortality exclusively in patients with PS Grade 0. In the same baseline calcium range, a significant association was observed between reduced serum calcium levels and lower mortality only in patients with a history of ACVD or DN. Similarly, in patients with baseline serum phosphate levels of 5.0–<5.5 mg/dL, reduced serum phosphate levels were associated with lower mortality only in those with PS Grade 0, a history of ACVD or DN. These findings indicate that PS should be considered in treating mild hypercalcemia or hyperphosphatemia in hemodialysis patients. Moreover, stringent management of hypercalcemia and hyperphosphatemia in patients with a history of ACVD or DN might be associated with a better prognosis.